Studies on Schismatoglottideae (Araceae) of Borneo XXX — New species and combinations for Bucephalandra - Wong, Sin Yeng; Boyce, P.C (BGBM Berlin-Dahlem., 2014)
Nineteen new species of Bucephalandra Schott are described: B. akantha S. Y. Wong & P. C. Boyce, sp. nov., B. aurantiitheca S. Y. Wong & P. C. Boyce, sp. nov., B. belindae S. Y. Wong & P. C. Boyce, sp. nov., B. bogneri S. Y. Wong & P. C. Boyce, sp. nov., B. chimaera S. Y. Wong & P. C. Boyce, sp. nov., B. chrysokoupa S. Y. Wong & P. C. Boyce, sp. nov., B. diabolica S. Y. Wong & P. C. Boyce, sp. nov., B. forcipula S. Y. Wong & P. C. Boyce, sp. nov., B. goliath S. Y. Wong & P. C. Boyce, sp. nov., B. kerangas S. Y. Wong & P. C. Boyce, sp. nov., B. kishii S. Y. Wong & P. C. Boyce, sp. nov., B. minotaur S. Y. Wong & P. C. Boyce, sp. nov., B. oncophora S. Y. Wong & P. C. Boyce, sp. nov., B. pubes S. Y. Wong & P. C. Boyce, sp. nov., B. sordidula S. Y. Wong & P. C. Boyce, sp. nov., B. tetana S. Y. Wong & P. C. Boyce, sp. nov., B. ultramafica S. Y. Wong & P. C. Boyce, sp. nov., B. vespula S. Y. Wong & P. C. Boyce, sp. nov. and B. yengiae P. C. Boyce, sp. nov. Furthermore, three pre-existing species names are transferred from Microcasia Becc. to Bucephalandra: B. elliptica (Engl.) S. Y. Wong & P. C. Boyce, comb. nov. (≡ Microcasia elliptica Engl.), B. muluensis (M. Hotta) S. Y. Wong & P. C. Boyce, comb. nov. (≡ M. muluensis M. Hotta) and B. oblanceolata (M. Hotta) S. Y. Wong & P. C. Boyce, comb. nov. (≡ M. oblanceolata M. Hotta). Together these changes take Bucephalandra to 27 species. An updated generic description is provided, and a key to all species is offered. All species dealt with taxonomically and nomenclaturally are illustrated from living plants, and with comparative plates of the spadices. Where possible scientific names are correlated to nomenclature used by commercial suppliers. Remaining taxonomic problems are highlighted, and foci for further study suggested. Notes on the role of the motile interstice staminodes are supplied.